Dificultad en la comunicacion del riesgo de padecer cáncer hereditario - Blanco, Ignacio; González, Melinda (Psicooncología, 2005)
Different studies have highlighted that sometimes patients have difficulties understanding what the doctor wants to communicate to them. This article tries to explain which factors can affect the process of communicating risk to patients that have cancer family history or previous cases of.There are studies that prove how patients with family cases/history of cancer worry about the possibility of suffering this illness. However,only a few of them have explored how patients understand and perceive the concept of risk and the possible biases associated to it.As a first approach, we believe that it is necessary to use a simple, clear and easy language for patients to understand, escaping from the excessive epidemic or doctor language. It is also important to design psychoeducational programs and appropriate material for support,as well as a correct handling of counseling skills as the main tool of work, and to promote future investigations into this specific area.